Meta-analysis of Self-Adjustment Factors of Migrant Students in Indonesia - Permatasari, Nirwana; Suminar, Dewi Retno; Hendriani, Wiwin (Psychological Research on Urban Society, 2024)
The increasing trend of higher education has led to a desire for higher quality education among migrant students. Migrant students typically face a variety of challenges from the moment they leave home, including the need to adapt to both new cultures and norms, as well as new educational experiences. The purpose of this study is to examine the adjustment factors of migrant students in Indonesia by synthesizing findings from relevant studies. The method used is meta-analysis, this analysis explores the multifaceted relationship between various factors and the adjustment process of migrant students in the context of higher education in Indonesia. The procedure was to develop review questions, develop inclusion and exclusion criteria, conduct a literature search strategy, identify articles, abstract and assess the risk of bias, and synthesize findings. The databases used were Google Scholar, Garuda Portal and Microsoft Academic. There were 16 articles included in the inclusion category. The results showed that personality and intelligence factors, learning process factors, environmental factors and cultural factors significantly improved the adjustment of migrant students in Indonesia with pooled ORs of 0.48 (95% CI 0.36-0.59) for personality and intelligence factors, 0.52 (95% CI 0.33-0.72) for learning process factors, 0.35 (95% CI 0.21-0.50) for environmental factors, and -0.16 (95% CI -1.48-1.15) for cultural factors. By integrating insights from multiple sources, this meta-analysis provides a comprehensive understanding of the complexities involved in the adjustment of overseas students in Indonesia. The findings provide valuable insights for developing tailored support mechanisms, interventions, and policies to enhance the academic and social success of international students in higher education settings in Indonesia.